Wings of desire [videorecording (DVD)] - Knieper, Jürgen (Distributed by MGM Home Entertainment, 2003)
A romantic fantasy about an angel who wishes he were mortal and is willing to fall from the sky if it means a chance to fall in love. Set in modern day Berlin, the film follows angel Damiel's path from heavenly flight to earthly delight in a manner that's comical, touching and entertaining.